Stagflation and topsy-turvy capital flows - Julien Bengui; Louphou Coulibaly (Bank of Canada, 2022)
Are unregulated capital flows excessive during a stagflation episode? We argue that they likely are, owing to a macroeconomic externality operating through the economy's supply side. Inflows raise domestic wages through a wealth effect on labor supply and cause unwelcome upward pressure on marginal costs in countries where monetary policy is trying to drive down costs to stabilize inflation. Yet market forces are likely to generate such inflows. Optimal capital flow management instead requires net outflows, suggesting topsy-turvy capital flows following markup shocks.
Keywords: D62; E52; F32; F38; F41; 330; Inflation and prices; International financial markets; International topics; Monetary policy